The Influences Of Perceived Parental Care, Perceived Teacher Care And Caring Thinking On Moral Identity Among Adolescents With Disciplinary Problems - Shaari, Anis (2021)
This study aimed to examine whether perceived parental care and perceived teacher care influence adolescents’ caring thinking aspects (i.e., affective thinking, appreciative thinking, active thinking, normative thinking & emphatic thinking), which in turn posit as antecedents of MI.